2021
DOI: 10.21608/ejp.2021.109535.1050
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Copper Oxide and Magnesium Oxide Nanoparticles on Controlling Black Scurf Disease on Potato

Abstract: Black scurf disease caused by Rhizoctonia solani is common on potato crop worldwide. The current study aimed to evaluate the antifungal activity of CuONPs and MgONPs on R. solani in laboratory, greenhouse and field trials. Field trials were conducted under naturally infected fields located in two Governorates, Behera and Menoufia. Potato tubers cv. Spunta were soaked in different concentrations (75, 150 and 200 mg/L) of the tested NPs for 2 hours pre-planting. Disease severity (DS) and disease incidence (DI) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Copper nanoparticles were used against various fungal phytopathogens belonging to various genera, such as Alternaria, Macrophomina, Fusarium, Penicillium, Colletotrichum, Rhizoctonia, Phytophthora, and Botrytis (Gunalan et al, 2012;Sankar et al, 2014;Ismail, 2021). Rubina et al (2017) reported cytoplasmic loss, cytoplasmic coagulation, distortion, and destruction of fungal Our results demonstrated that CaO-NPs have no significant effect on the hyphal growth of S. rolfsii, while the effect of CaO-NPs was limited to the aggregation of sclerotia, which decreased sclerotial germination.…”
Section: Effects Of Cuo-nps On Fungal Growthmentioning
confidence: 78%
“…Copper nanoparticles were used against various fungal phytopathogens belonging to various genera, such as Alternaria, Macrophomina, Fusarium, Penicillium, Colletotrichum, Rhizoctonia, Phytophthora, and Botrytis (Gunalan et al, 2012;Sankar et al, 2014;Ismail, 2021). Rubina et al (2017) reported cytoplasmic loss, cytoplasmic coagulation, distortion, and destruction of fungal Our results demonstrated that CaO-NPs have no significant effect on the hyphal growth of S. rolfsii, while the effect of CaO-NPs was limited to the aggregation of sclerotia, which decreased sclerotial germination.…”
Section: Effects Of Cuo-nps On Fungal Growthmentioning
confidence: 78%
“…Recent findings from [57] showed that lentil (Lens culinaris) plants treated with various doses of CuO-NPs have elevated APX and SOD activity (0.01, 0.025, and 0.05 mg mL −1 ). Additionally, 20 days after planting, potato plants treated with CuO-NPs at a dosage of 200 mg L −1 showed an increase in PO and PPO activity [58].…”
Section: Antioxidant Enzymesmentioning
confidence: 97%
“…According to [61], field-testing with CuO-NPs at 200 µL L −1 resulted in a 100% decrease in the Rhizoctonia solani-caused black scurf disease. Copper-based NPs showed promise in preventing Phytophthora infestans-caused tomato late blight [62], as well as a number of fungal diseases such as A. alternata and Botrytis cinerea [63], tomato Fusarium wilt [64], and black scurf disease in potato [58].…”
Section: Disease Incidence Percentmentioning
confidence: 99%
“…The mechanism of definition against microbial pathogens initiates with the induction of defense enzymes such as PPO, deposition of the cell wall, and hypersensitive response (26). CuO NPs and MgO NPs had a great impact on increasing the enzyme activities of PPO (Ismail 2021). Treated with ZnO NPs increased the activities of PPO enzyme defense (16).…”
Section: Determination Of Polyphenol Oxidase Enzyme (Ppo)mentioning
confidence: 99%